Hambatan Guru IPA Kelas VII dalam Mengimplementasikan Kurikulum 2013-revisi Se-Kotamadya Bandar Lampung - Eka Fitrianingsih; Arwin Achmad; Rini Rita T. Marpaung (Universitas Lampung, 2018)
This study aims to describe the problems of science teachers of class VII on implementing K13-revision. Sampling used purposive sampling technique. Types of research used was descriptive research, data were obtained from questionnaire and interview, then analyzed descriptively. The results showed that the implementation of K13-revision in the academic year 2016/2017 in Bandar Lampung Municipality of five aspects, aspects that indicated the obstacles were(1) learning text (2) process and implementation of learning that has a percentage of 30%. Both of these aspects had the category of